Co-offending and Criminal Careers in Organized Crime - Meneghini, Cecilia (Journal of developmental and life-course criminology, 2022)
The growing research on co-offending over the life course is based on relatively small, general offending samples, followed for a short period, and from a limited set of countries. This study expands current knowledge by examining the relation of co-offending with age, criminal experience, crime type, and crime seriousness in a large sample of Italian serious organized crime offenders with criminal careers spanning between age 14 and late adulthood. The sample includes 160,262 offenses by 10,530 Italian mafia offenders. After preliminary descriptive statistics, random-effects logistic regressions estimate how age, criminal experience, crime type, and seriousness are independently related to the co-offending probability. Co-offending decreases only moderately with both the age and criminal experience of organized crime offenders, while more prolific offenders exhibit a stable co-offending prevalence as their experience increases. Co-offending varies significantly by crime type, and it is more frequent for more serious offenses. In line with previous research, co-offending has a relevant functional component even for organized crime offenders: results suggest it is instrumental to perpetrating specific offense types and more serious offenses. However, results also show that specific social and criminal contexts promote co-offending among older and more experienced offenders.